Pengaruh Switching Cost dan Switching Intention Terhadap Word-Of-Mouth Terhadap Konsumen Provider Seluler Telkomsel di Kota Denpasar - Pradnyawati, Made Ayu Nata; Suasana, I Gusti Agung Ketut Gede (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
Normal 0 false false false IN X-NONE X-NONE The aim of this research was to find out the impact of switching cost and switching intention toward word-of-mouth on provider service Telkomsel’s consumer in Denpasar. The data that used in this research collected by distributing questionnaires to 110 respondents in Denpasar. Path analysis was used to analyze the hypothesis’ in this study. Based on statistical calculation, hypothesis one is supported because switching cost significantly impacts switching intention, switching intention significantly impacts word-of-mouth, and switching cost significantly im pacts word-of-mouth on Telkomsel’s consumer, so that hypothesis two and three are supported. The implications of this study for the company is Telkomsel’s consumer can be maintained as long as switching costs increase and be considered as switching barriers. Keywords: switching cost, switching intention, word-of-mouth
Keywords: Switching Cost; Switching Intention; Word-Of-Mouth